(3GdHQgGf aj JhLjg eJTGHg GdbQBf deG ajg ef GdMLI hGdHjGfs - (3GdcQeGfj , HQgGf GdOjf CHh GdbGSe eMehO Hf MeRI Hf fUQ GdcQeGfj GdebQj GdTGaYj, JGL GdbQGA,J (B505 (3g` s ((3eOjfI MeU s)
(3ChdgG (B:s
,(3HYO agPG cJGH GPcQ ajg GdGjGJ GdeJTGHgGJ GdJi JcQQJ ai GdbQGf hCdaGXgG eJabg dcf hbY ai HYVgG RjGOI Ch fbUGf Gh JbOje s
(3BNQgG (B:s
(3CSHGH GNJUGU cd ShQI HeG GTJedJ Ydjg Ohf GdShQ GdGNQi HMjK de jJHb ddRGjZ ajg ebGd hdG dWYf GdWGYf ajg eLGd hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B168 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B161s
Keywords: (3GdJaSjQ hYdhe GdbQBfs